Upaya Hukum Tata Usaha Negara Terhadap Polemik Penganugerahan Gelar Kehormatan Akademis - Efendi, Virga Dwi; Yossyafaat, Herkin (Media Iuris, 2024)
The awarding of honorary academic degrees in the form of a chancellor's decision always gives rise to positive and negative assessments from academics and the public. The aim of this research is to analyze the chancellor's decision regarding the awarding of honorary academic degrees regarding the qualifications for the State Administrative Decree (KTUN) which is the absolute competence of the State Administrative Court (PTUN) as well as legal remedies for the polemic that arises as a result of the issuance of this decision. Next we will explain the efforts law regarding disputes that arise as a result of the rector's decision. This research uses a type of juridical-normative legal research with a historical, conceptual and normative approach. The results of this research show that the rector's decision regarding the awarding of academic honorary degrees, both honoris causa doctoral degrees and professorial degrees. Honor is a State Administrative Decision (KTUN) and is included in the absolute authority of the PTUN so that if a dispute arises, the resolution can be reached through the PTUN. The conditions for granting honorary academic degrees are the result of accumulated historical thought and experience in the legal dynamics that govern it. The legal remedies for the emergence of TUN disputes related to the chancellor's decision regarding academic honorary degrees are the same as resolving KTUN disputes in general, namely through administrative efforts or litigation efforts through the PTUN.